2022
DOI: 10.1136/ard-2022-222935
|View full text |Cite
|
Sign up to set email alerts
|

Low copy numbers of complementC4andC4Adeficiency are risk factors for myositis, its subgroups and autoantibodies

Abstract: BackgroundIdiopathic inflammatory myopathies (IIM) are a group of autoimmune diseases characterised by myositis-related autoantibodies plus infiltration of leucocytes into muscles and/or the skin, leading to the destruction of blood vessels and muscle fibres, chronic weakness and fatigue. While complement-mediated destruction of capillary endothelia is implicated in paediatric and adult dermatomyositis, the complex diversity of complement C4 in IIM pathology was unknown.MethodsWe elucidated the gene copy numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…Luo et al (28) showed that the peripheral plasma concentration of C3 and C3a was significantly higher in the major depressive disorder group than in the healthy controls; Crider et al (29) showed a significant increase in C3 expression in the prefrontal cortex of depressed suicide patients, and C4A is essential for the propagation of the classical complement pathway. Genetic deficiencies of C4A are the monogenic causative factors for the prototypic autoimmune disease systemic lupus erythematosus (30); Zhou et al (31) showed that C4A deficiency is a risk factor for myositis, its subgroups and autoantibodies. To our knowledge, there are no reports on C4A expression in depression.…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al (28) showed that the peripheral plasma concentration of C3 and C3a was significantly higher in the major depressive disorder group than in the healthy controls; Crider et al (29) showed a significant increase in C3 expression in the prefrontal cortex of depressed suicide patients, and C4A is essential for the propagation of the classical complement pathway. Genetic deficiencies of C4A are the monogenic causative factors for the prototypic autoimmune disease systemic lupus erythematosus (30); Zhou et al (31) showed that C4A deficiency is a risk factor for myositis, its subgroups and autoantibodies. To our knowledge, there are no reports on C4A expression in depression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, low copy numbers of complement C4 and low C4 protein levels were related to the presence of anti-Ro/La, anti-Jo1, and anti-PM/Scl in IIM. 28 , 29 Since these C4 associations are not completely independent from the association with HLA-DRB1∗03 , both types of genetic variations may contribute independently and interactively to the autoantibody-defined IIM subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Our results reinforce the idea that rheumatic diseases share similar genetic risk factors (i.e., HLA ) which predispose to certain autoantibody specificities and that there is a reciprocal relationship between specific genetic HLA variations and the presence of particular autoantibodies. 26 , 27 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“… 31 Finally, there are reports of complement C4 deficiencies with active myositis, suggesting that evaluating C3 and C4 levels may be beneficial. 32 …”
Section: Diagnosismentioning
confidence: 99%